Geological And Geotechnical Characterization Of The Beni Moussa Perimeter In The Tadla Plain(Morocco) - Achraf, Kharmouch; Abdessamad, Najinea; Amina, Wafik (European Scientific Journal, ESJ, 2020)
The Beni Moussa perimeter in the plain of Tadla is located in the Beni Mellal - Khenifra region characterized by the diversity of its relief where the mountain meets the plain through the foothills. Bibliographic studies raise the dominance of limestone formations in the Atlas ranges of this region, and the piedmont accumulates alluvium deposited by rivers, while the plain is filled with mio-plio-quaternary deposits. A series of seven drill holes of various depths, supplemented by pressuremeter measurements every 1.50m of depth using the Menard pressuremeter, was carried out on sites scattered around the perimeter of the Beni Moussa in the plain of Tadla, to validate at first the bibliographic geological models, then to appreciate the bearing capacity of the lithologies revealed. The lithological sections thus revealed an alternation of alluvial deposits, clays and clay loams, deposited on calcareous formations, resulting from the dolomitic and calcareous mountainous debris mobilized following the seasonal temperature’s variation of the region. Moreover, the measured pressurometric ranges characterize a generally high bearing capacity, and reflect the generalized overconsolidation of the facies and soils encountered in the Beni Moussa area, except for the Middle Pleistocene formations, which are mainly characterized by channeled conglomeratic deposits.This study’s datathus reflect a good bearing capacity of the ground formations, capable of supporting the superstructures founded in this perimeter.